CHROMIUM SCHREYERITE AND CHROMIUM-VANADIUM-MANGANESE-IRON-ZINC SPINEL IN QUARTZITIC SILLIMANITE-CORDIERITE SCHISTS OF THE OLKHON AREA SOUTHWEST OF LAKE BAIKAL - Boronikhin V.A.; Dmitriyeva M.T.; Koneva A.A.; Korikovskiy S.P. (My University, 1990)
New vanadium minerals recently discovered in metamorphic rocks and pyrite ores include schreyerite, V2Ti3O9, and vuorelainenite (Mn, Fe)V2O4, the end member of the chromium-vanadium manganospinel series. We succeeded in finding both these coexisting minerals in high-alumina schists of the Ol'khon area. Our schreyerite is a hitherto unknown high-chromium variety, but the spinel is the variety intermediate between vuorelainenite (sic) and manganochromite. This paper discusses the mineralogy of these finds.